Sistem Perencanaan Instalasi Listrik Rumah Tinggal Dengan Metode RAD - Saputro, Andi; Permatasari, Hanifah; Atina, Vihi (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
This research aims to analyze, design, and develop a web-based information system to calculate the cost of electrical installation for simple residential homes using the Rapid Application Development (RAD) method. The research background is the need for a system that can facilitate users in planning and estimating electrical installation costs based on technical specifications and power requirements. The system is designed to provide accurate cost estimates, including the cost of installing electrical points, sockets, lights, and other electrical components, enabling users to make more informed decisions. The RAD method is employed to accelerate the development process and ensure the system meets user needs through rapid iterations and prototyping. The results indicate that the system can deliver precise and user-friendly cost calculations, making it an effective tool for planning electrical installations in simple residential homes.